Discovering and Listing of Elements of Deleuze’s Philosophy of Immanence as a Research Approach - Farhad Bamdad; Yahya Ghaedi; Saeid Zarghami-Hamrah; Mehran Farajollahi (International Journal of Psychosocial Rehabilitation, 2020)
Philosophy of immanence is one of the two major currents of post-structuralist philosophy in France. This philosophy in its Deleuzian approach encounters with phenomena in a way that on the basis of which one can discuss the problem of knowledge without leading oneself outside the phenomenal world or any other type of transcendence. The problem of present study is that although Deleuze like other poststructuralists has not formulated and enumerated the elements of his own philosophical approach, since this approach struggles to find an answer from inside to the problem without any transcendence and this can also be seen in the thought of Deleuze, one can make efforts towards the discovery of a research approach based on his thought. Accordingly, this essay is devoted to the study of Deleuze’s philosophy and its foundations through the examination of the background and short history of the philosophy of immanence from the point of view of his definition of major philosophical disciplines (ontology and epistemology) and his work on other philosophers (Spinoza, Kant, Hume and Nietzsche). Then, having studied the nature of philosophical research, it seeks to show that we can search for such elements as research approach based on Deleuzian thought. Finally, it will be focused on the discovery and enumeration of the elements of Deleuze’s research approach. The authors have found four elements through which one can conduct a research: 1. Autarky of a phenomenon, 2. Univocity of a phenomenon, 3. Cognition of a phenomenon based on radical empiricism and 4. Restricted Creativity.